Interleukin 13 blocks the release of collagen from bovine nasal cartilage treated with proinflammatory cytokines - Cleaver, C (2001)
OBJECTIVE—To investigate whether interleukin 13 (IL13) could act in a chondroprotective manner and protect cartilage stimulated to resorb with a combination of IL1α and oncostatin M (OSM), in a similar way to the anti-inflammatory cytokine, IL4. METHODS—IL13 was added to explant cultures of bovine nasal cartilage stimulated to resorb with IL1α and OSM, and the release of collagen and proteoglycan determined. Collagenolytic and tissue inhibitors of metalloproteinase (TIMP) activities were determined by bioassay. Northern blot analyses were performed to determine the effects of IL13 on the induction of matrix metalloproteinase-1 (MMP-1), MMP-3, MMP-13, and TIMP-1 gene expression. RESULTS—IL13 can prevent the release of collagen from bovine nasal cartilage in a dose dependent manner. This was accompanied by a concomitant decrease in measurable collagenolytic activity in the culture supernates and an increase in TIMP activity. Northern blot analysis showed that IL13 down regulated MMP-3 and MMP-13 levels but up regulated MMP-1 and TIMP-1 gene expression in bovine nasal chondrocytes at 24( )hours. CONCLUSION—This study showed for the first time that IL13 can block collagen release from resorbing cartilage in a similar manner to IL4. This is accompanied by a reduction in detectable collagenolytic activity, a decrease in MMP-3 and MMP-13 mRNA levels, and an up regulation of TIMP-1 expression.